Development and implementation of a sensitivity training curriculum focused on equity in healthcare - Allen M. Chen (Learning Health Systems, 2025)
Abstract Purpose A longitudinal sensitivity‐based curriculum focused on diversity, equity, and inclusion (DEI) and consisting of interactive seminars and roundtable discussions was constructed to equip participants with tools to enhance culturally effective care and to create an inclusive learning environment. The purpose of this study was to report our single‐institutional experience with the development and implementation of this evidence‐based curriculum. Methods and Materials Core DEI themes on which to center the sensitivity training curriculum were identified through an evidence‐based review based on the Preferred Reporting Items for Systematic Review and Meta‐Analysis Protocols (PRISMA‐P) statement. A MEDLINE search was undertaken to identify original peer‐reviewed works using the items “equity, diversity, inclusion,” “underserved,” “disadvantaged,” “sensitivity training,” and “curriculum.” Results Based on the search results, a 12‐month curriculum was established centered on the core themes that emerged. The 98 peer‐reviewed publications chosen to develop this thematic framework could be broadly categorized as follows: health disparities (N = 33); workplace diversity (N = 24); implicit bias (N = 21); and structural racism (N = 20). Between November 2022 and January 2024, a total of 12 interactive sessions were scheduled. The mean number of attendees for each DEI session was 19 (range: 3 to 32), and the mean length of each session was 50 min (range: 20 to 81). Conclusion The developed curriculum helped promote awareness of historical inequities in healthcare and empowered learners to become better advocates for colleagues and patients alike. The implication for healthcare leaders are discussed.